Prediction of Basketball Shooting Ability on the Basis of Anthropometric Characteristics, Wrist Range of Motion, and Strength of Upper Extremity in Elite Female Basketball Players - Nahid Adibpour; Leila Ghazaleh; Farzaneh Hatami (Biyumikānīk-i varzishī, 2016)
Objective: This study aims to predict basketball shooting ability on the basis of anthropometric characteristics, wrist range of motion, and strength of upper extremity in elite female basketball players.